Product backlog orientado a metas em projetos scrum para fundamentar as tomadas de decisões do product owner - Soares, Renato Mesquita (2020)
In the Scrum Framework, the Product Owner (PO) takes the central role within the development process, being responsible for communicating between the customer and the developers. In this intermediation, he manages the Product Backlog, which maintains a list of items to be developed, corresponding to the customer’s needs. In this sense, the literature has explored the challenges of the PO, mainly in the planning activities where, in this context, the decision making is seen as his most important task. However, the lack of structured information that can support their choices, makes them, many times, make wrong decisions or omit this responsibility. In Goal-Oriented Requirements Engineering, the requirements are described from the stakeholders organizational goals and, according to the literature, their definition can bring several benefits in terms of information organization capacity. Most Scrum projects use user stories to specify requirements and, although they contain the definition of the goal, it is not evidented in the development process. That said, this work aims to provide a presentation of the organizational information, inherent to the desired product or service, in a provision that justifies and guides the decision making of the PO. To this end, a new model, the Goals-Oriented Product Backlog, was proposed, which seeks to highlight the goals and their relationships with user stories. The evaluative study carried out found evidence that the artifact provides more structured information to the PO and, consequently, contributes to his decision making.